2022
DOI: 10.3748/wjg.v28.i28.3608
|View full text |Cite
|
Sign up to set email alerts
|

Potassium-competitive acid blockers and gastroesophageal reflux disease

Abstract: Proton pump inhibitors (PPIs), the most commonly used antisecretory medi-cations in the management of reflux illness, virtually eliminate elective surgery for ulcer disease, and relegate anti-reflux surgery to patients with gastroesophageal reflux disease (GERD) who are inadequately managed by medical therapy. However, PPI medications still leave some therapeutic demands of GERD unmet. Furthermore, up to 40%-55% of daily PPI users have chronic symptoms, due to PPI refractoriness. Potassium-competitive acid blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 68 publications
0
5
0
1
Order By: Relevance
“…ИПП -основные препараты для лечения ГЭРБ, пищевода Барретта, эозинофильного эзофагита, функциональной диспепсии, хронического гастрита, для профилактики и лечения гастропатий, ассоциированных с применением нестероидных противовоспалительных препаратов (НПВП) [28]. Наиболее продолжительные курсы терапии используют для лечения заболеваний пищевода -ГЭРБ, пищевод Барретта, эозинофильный эзофагит [29,30].…”
Section: показания к применению ингибиторов протонной помпыunclassified
“…ИПП -основные препараты для лечения ГЭРБ, пищевода Барретта, эозинофильного эзофагита, функциональной диспепсии, хронического гастрита, для профилактики и лечения гастропатий, ассоциированных с применением нестероидных противовоспалительных препаратов (НПВП) [28]. Наиболее продолжительные курсы терапии используют для лечения заболеваний пищевода -ГЭРБ, пищевод Барретта, эозинофильный эзофагит [29,30].…”
Section: показания к применению ингибиторов протонной помпыunclassified
“…20 However, potassium-competitive acid blockers (P-CABs) can bind to both resting and activated H + /K + -ATPase, which has a greater acid-suppressive efficacy. 21 P-CABs can be stabilized in the acidic environment of the stomach for at least 8 h, do not need to be formulated into enteric-coated preparations, and absorption is not affected by food. It is mainly metabolized by cytochrome P450 (CYP) 3A4, and the inhibition of acid is less affected by CYP2C19 polymorphism.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a randomized, 3‐period study found tegoprazan produced more rapid, potent and well sustained night‐time acid suppression vs vonoprazan or esomeprazole when administered at night 20 . However, potassium‐competitive acid blockers (P‐CABs) can bind to both resting and activated H + /K + ‐ATPase, which has a greater acid‐suppressive efficacy 21 . P‐CABs can be stabilized in the acidic environment of the stomach for at least 8 h, do not need to be formulated into enteric‐coated preparations, and absorption is not affected by food.…”
Section: Introductionmentioning
confidence: 99%
“…GERD may also present with atypical features such as chronic cough, chest pain, dental erosions, laryngitis or asthma. [3][4][5] GERD may be classified as erosive esophagitis (EE), non-erosive reflux disease (NERD), and Barrett esophagus (BE). 6 Of these 3 phenotypes, NERD is the most prevalent (60-70%), followed by EE (30%) and BE (6-12%).…”
Section: Introductionmentioning
confidence: 99%